2008
DOI: 10.1227/01.neu.0000327023.18220.88
|View full text |Cite
|
Sign up to set email alerts
|

Techniques and Complications of External Lumbar Drainage for Normal Pressure Hydrocephalus

Abstract: The rate of serious complications from external lumbar drainage for normal pressure hydrocephalus is low. It is hoped that continued evaluation of the procedure will lead to further reductions in the complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 12 publications
0
77
2
6
Order By: Relevance
“…The risk factors associated with these drains include disconnection of the external drainage system and the presence of other infections. In a study involving 233 consecutive patients who underwent placement of an external lumbar drain for normal-pressure hydrocephalus testing, the rate of meningitis was low (0.8%) [22]. The investigators in that study used a strict protocol that called for no surveillance testing of CSF, drainage of CSF for a maximum of 5 days, sterile reconnection after disconnection or fracture of the drain, and permanent removal of the drain after a second disconnection or fracture.…”
Section: Cerebrospinal Fluid Drainsmentioning
confidence: 99%
“…The risk factors associated with these drains include disconnection of the external drainage system and the presence of other infections. In a study involving 233 consecutive patients who underwent placement of an external lumbar drain for normal-pressure hydrocephalus testing, the rate of meningitis was low (0.8%) [22]. The investigators in that study used a strict protocol that called for no surveillance testing of CSF, drainage of CSF for a maximum of 5 days, sterile reconnection after disconnection or fracture of the drain, and permanent removal of the drain after a second disconnection or fracture.…”
Section: Cerebrospinal Fluid Drainsmentioning
confidence: 99%
“…Extended lumbar drain (LD) for 72 hours has become a popular pre-shunt workup in many neurosurgical centers [59][60][61]. Its popularity stems from the findings of an excellent study which demonstrated the high specificity and sensitivity of predicting shunt response based on LD test outcome [60,62].…”
Section: Predicting Lumbar Drain Outcome From Icp Morphologymentioning
confidence: 99%
“…The risk of meningitis associated with lumbar drain placement varies from 0% to 25.6% [14], and is highest when the drain is placed after subarachnoid or intraventricular hemorrhage, after disconnection of external drainage system, or in the presence of other infections.…”
Section: External Lumbar Cathetersmentioning
confidence: 99%